Digital Library and Institutional Repository for Supporting Information Literacy - Munawaroh, Munawaroh; Prayitno, Dio Eka (Universitas Airlangga, 2015)
Development of information technology, easy to get from smartphone or personal digital assistant (PDA) influence behavioral users to access information at library, that change behavioral users to access information effect of habit usersâEvery time with smartphoneâ. Example Users want to get information from book, they will copy or note but now they just take with their smartphone and access information from library they use laptop, gadget which connection internet. This condition a lot of librarian to develop their library became âDigital Libraryâ (DL) and âInstitutional Repositoryâ (IR). The goal of DL and IR are to provide information which more easy to access, especially local contents the